1998
DOI: 10.1002/(sici)1097-4636(199823)43:3<215::aid-jbm1>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Effects of new machinable ceramic on behavior of rat bone cells cultured in vitro

Abstract: The behavior of cultured rat bone cells growing on modified polyethylene terephthalate (mPET), glass, and machinable ceramic substrates containing enstatite (MgO, SiO 2 ) and glass (CaO-P 2 O 5 -Al 2 O 3 ) was studied. Cell attachment was measured directly on the substrates using an image analysis system. Electron microscopy observations and the MTT test revealed that cells are able to spread and proliferate on the material surface, keeping a healthy ultrastructure on all materials tested in the present study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Osteogenic cells from newborn rat calvaria, which have been shown to produce mineralized tissue on standard culture dishes,5, 13–16 were cultured on HA‐ and Ti‐coated surfaces. The method used for osteoblast culture has been described previously 17, 18.…”
Section: Methodsmentioning
confidence: 99%
“…Osteogenic cells from newborn rat calvaria, which have been shown to produce mineralized tissue on standard culture dishes,5, 13–16 were cultured on HA‐ and Ti‐coated surfaces. The method used for osteoblast culture has been described previously 17, 18.…”
Section: Methodsmentioning
confidence: 99%
“…Clinoenstatite was reported as one of the four polymorphic forms of MgSiO 3 (enstatite, protoenstatite, clinoenstatite, and high‐temperature clinoenstatite) 11–15 . The sol–gel synthesis, 16–18 modified pechini, 19 precipitation method, 20,21 and solid‐state reaction methods 11,22–25 have been used to synthesize MgSiO 3 powders. Merle and colleagues 22–25 fabricated enstatite bioceramics with 5–15 wt% Ca–P glass or Ca–P–Al glass component, and the studies showed that the materials possessed good cell biocompatibility and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%